PEMENUHAN HAK ISTRI PASCA PERCERAIAN DILUAR PENGADILAN AGAMA DI DESA SINAR LAUT KABUPATEN CIANJUR - Novitasari Novitasari; Prahasti Suyaman (JOURNAL OF LAW AND NATION, 2024)
Marriage is a physical and mental union between husband and wife, which connects the two of them who were originally two different human individuals. The method used in the research is a descriptive method with a qualitative approach. The type of legal research conducted is Juridical Empirical, namely legal research that examines applicable legal regulations and the reality that occurs in society, this research is conducted to understand the actual situation that occurs in society, with the aim of finding facts used as research data, then the data is analyzed to identify problems that ultimately lead to problem solving. This research was conducted in Sinar Laut Village, and the Religious Affairs Office (KUA) of Agrabinta District, Cianjur Regency. Data collection techniques in this research are observation, interviews, documentation and literature study. The results showed that divorce outside the religious court carried out by the people of Sinar Laut Village illustrates a form of injustice in the fulfillment of wives' rights, this is caused by five factors including Many women do not know their rights such as iddah and mut'ah maintenance, as well as legal procedures for filing divorces in court, long distances to the court and high costs are the main obstacles, coupled with the complicated and time- consuming divorce process, Economic dependence on husbands or in-laws leaves women without the resources to claim their rights after divorce, Influence from husbands and in-laws and concerns about family reputation often prevent women from claiming their rights through legal channels, and cases of domestic violence and irresponsible behavior from husbands exacerbate women's conditions, yet they still do not receive adequate legal protection. The results also show that the role of the Village Head, KUA, and Amil is crucial in addressing and reducing cases of out-of-court divorce by socializing to the community the negative impact of out-of-court divorce on the rights of the wife and children as well as other administrative aspects.